2005
DOI: 10.1590/s1415-47572005000100019
|View full text |Cite
|
Sign up to set email alerts
|

A study of the constitutive heterochromatin and nucleolus organizer regions of Isocopris inhiata and Diabroctis mimas (Coleoptera: Scarabaeidae, Scarabaeinae) using C-banding, AgNO3 staining and FISH techniques

Abstract: Meiotic and mitotic chromosomes of Isocopris inhiata and Diabroctis mimas were studied by standard staining procedures, C-banding, silver nitrate staining and FISH using Apis mellifera 28S rDNA as probe. Isocopris inhiata presented a 2n = 18 (8II+ Xy p ) karyotype, composed of meta-submetacentric chromosomes with gradual reduction in size. The karyotype of D. mimas was 2n = 20 (9II+ Xy p ), composed of meta-submetacentric (pairs 1, 2, 3, 4 and 7) and acrocentric (pairs 5, 6, 8 and 9) chromosomes, with gradual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 25 publications
9
56
0
Order By: Relevance
“…On the other hand, some species had small additional blocks, as observed in D. geminatus, as was reported in Scarabaeidae (that is, Bubas bison) (Colomba et al, 2006) and Aphodius representative species (Wilson and Angus, 2004). Moreover, in species belonging to the subfamily Scarabaeinae, large heterochromatic blocks were observed, as described for Diabroctis mimas and Isocopris inhiata (Bione et al, 2005b). These distinct patterns of heterochromatin distribution indicate that repetitive DNA sequences in Scarabaeidae are likely to show different dynamic processes of spreading governed by amplification and dispersion, through translocation of these elements, which is favored by chromocenter formation and ectopic heterochromatic associations.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…On the other hand, some species had small additional blocks, as observed in D. geminatus, as was reported in Scarabaeidae (that is, Bubas bison) (Colomba et al, 2006) and Aphodius representative species (Wilson and Angus, 2004). Moreover, in species belonging to the subfamily Scarabaeinae, large heterochromatic blocks were observed, as described for Diabroctis mimas and Isocopris inhiata (Bione et al, 2005b). These distinct patterns of heterochromatin distribution indicate that repetitive DNA sequences in Scarabaeidae are likely to show different dynamic processes of spreading governed by amplification and dispersion, through translocation of these elements, which is favored by chromocenter formation and ectopic heterochromatic associations.…”
Section: Discussionsupporting
confidence: 66%
“…The presence of only one nucleolar organizer region site detected by silver nitrate staining in D. geminatus does not correspond to the real genome organization of 45S rDNA clusters (2 clusters of 18S rDNA detected by FISH). The presence of more than one 45S rDNA site was observed in other Scarabaeinae species, such as Bubas bison (Colomba et al, 2006) and D. mimas (Bione et al, 2005b), and in unrelated groups of Coleoptera, such as Cicindelidae and Scarabaeidae as a whole, indicating more than one dispersion event of rDNA sequences.…”
Section: Mapping Of Repetitive Dnas In D Geminatus Dc Cabral-de-mellmentioning
confidence: 94%
“…The absence of chromosome polymorphisms in E. caribaeus indicates that presumably its diploid number reduction occurred in one ancestral population, before the dispersion process of this species. The reduced chromosome number of E. caribaeus is probably the resultant of pericentric inversions followed by fusions (Cabralde-Mello et al 2007), as observed in other species belonging to Scarabaeidae, for instance, Bubas bubalus 2n = 18, Xy (Angus et al 2007), Dichotomius geminatus 2n = 18, Xy p , (Cabral-de-Mello et al 2008), Isocopris inhiata 2n = 18, Xy p (Bione et al 2005a), and Macraspis festiva 2n = 18, Xy p (Bione et al 2005b). In some Scarabaeidae species, reduction in the diploid number caused by fusion between autosomes and autosome-X has been observed.…”
Section: Discussionmentioning
confidence: 83%
“…Meanwhile, particular cases of CH distribution have been reported in some Scarabaeidae; Cetonia aurata and Bubas bison have CH blocks located in the terminal region of eight autosomal bivalents, in addition to the pericentromeric blocks (Colomba et al 1996(Colomba et al , 2006Dutrillaux et al 2006). In some species of Scarabaeidae, such as Diabroctis mimas and Isocopris inhiata, the occurrence of diphasic chromosomes that present one heterochromatic and another euchromatic arm has been described (Bione et al 2005a). In addition to these patterns, there are still some species with almost total heterochromatic chromosomes or with CH absence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation